2006
DOI: 10.1091/mbc.e06-03-0232
|View full text |Cite
|
Sign up to set email alerts
|

TheNeurospora crassaWhite Collar-1 dependent Blue Light Response Requires Acetylation of Histone H3 Lysine 14 by NGF-1

Abstract: Blue light-induced transcription in Neurospora crassa is regulated by the White Collar-1 (WC-1) photoreceptor. We report that residue K14 of histone H3 associated with the light-inducible albino-3 (al-3) promoter becomes transiently acetylated after photoinduction. This acetylation depends on WC-1. The relevance of this chromatin modification was directly evaluated in vivo by construction of a Neurospora strain with a mutated histone H3 gene (hH3 K14Q ). This strain phenocopies a wc-1 blind mutant and shows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 57 publications
7
81
1
1
Order By: Relevance
“…Previously, it was reported that K14 of H3 is an activation mark for light-induced gene expression in the filamentous fungus Neurospora crassa (30). Therefore, by ChIP analysis we studied this modification for the promoter of the sterigmatocystin regulatory gene aflR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was reported that K14 of H3 is an activation mark for light-induced gene expression in the filamentous fungus Neurospora crassa (30). Therefore, by ChIP analysis we studied this modification for the promoter of the sterigmatocystin regulatory gene aflR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in N. crassa, mutation of the GCN5 homologue ngf-1 results in loss of repression of the blue-light-responsive al-3 gene in the dark (18). An ngf-1 RIP1 mutant was found to express al-3 constitutively, suggesting that the HAT is involved not only in blue-light FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in Neurospora crassa established that blue light-induced transcription of the early light-inducible genes al-3 and vvd depends on increased acetylation of histone H3 at lysine K14 (H3K14) in the promoters of these genes (18). The authors showed that acetylation and transient gene activation require the N. crassa GCN5 homologue ngf-1, and it was suggested that the specific activator, White Collar-1, is required for the recruitment of NGF-1 to al-3 and vvd promoters.…”
mentioning
confidence: 99%
“…Changes in chromatin structure may lead to short-or long-term alterations of the transcriptional activities of genes, and thus they are crucial for cell differentiation, metabolite production (126), and environmental adaptation (127). Epigenetic and chromatin rearrangement data obtained for higher eukaryotes or microorganisms such as yeast are often not applicable to filamentous fungi.…”
Section: Chromatin Structure Rearrangement and Histone Modificationmentioning
confidence: 99%